Gut microbiota associations with chronic kidney disease: insights into nutritional and inflammatory parameters - Lazarevic, Vladimir; Teta, Daniel; Pruijm, Menno; Stoermann, Catherine; Marangon, Nicola; Mareschal, Julie; Solano, Raquel; Wurzner-Ghajarzadeh, Arlene; Gaïa, Nadia; Cani, Patrice D.; Dizdar, Oğuzhan S.; Herrmann, François R.; et al. (Frontiers in Microbiology, 2024)
Introduction The gut barrier, comprising gut microbiota, plays a pivotal role in chronic kidney disease (CKD) progression and nutritional status. This study aimed to explore gut barrier alterations in hemodialyzed (HD) patients, non-HD (NHD) CKD patients, and healthy volunteers. Methods Our cross-sectional study enrolled 22 HD patients, 11 NHD patients, and 11 healthy volunteers. We evaluated fecal microbiota composition (assessed via bacterial 16S rRNA gene sequencing), fecal IgA levels, surrogate markers of gut permeability, serum cytokines, appetite mediators, nutritional status, physical activity, and quality of life. Results HD patients exhibited significant alterations in fecal microbiota composition compared to healthy volunteers, with observed shifts in taxa known to be associated with dietary patterns or producing metabolites acting on human host. In comparison to healthy volunteers, individuals with HD patients exhibited elevated levels of inflammatory markers (CRP, IL-6 and TNF-α), glucagon-like peptide-2, and potential anorexigenic markers (including leptin and peptide YY). NHD patients had increased levels of CRP and peptide YY. Overall fecal microbiota composition was associated with height, soft lean mass, resting energy expenditure, handgrip strength, bone mineral content and plasma albumin and TNF-α. Discussion Compared to healthy volunteers, HD patients have an altered fecal microbiota composition, a higher systemic inflammation, and a modification in plasma levels of appetite mediators. While some differences align with previous findings, heterogeneity exists likely due to various factors including lifestyle and comorbidities. Despite limitations such as sample size, our study underscores the multifaceted interplay between gut microbiota, physiological markers, and kidney function, warranting further investigation in larger cohorts.